MODEL OF THE GEOLOGICAL EXPLORATION PROCESS AND THE RANKING OF DEPOSITS - Bulkin G.A. (My University, 1989)
Study of the ranking of deposits in order of diminishing reserves has led to the development of a method for predicting the resources of such deposits. The reserves in such series are described by a hyperbolic distribution, with the parameters of such distributions, determined from empirical data, differing significantly from those determined from the theory that uses an evolutionary model of ore deposition. The author postulates that the GEP on the whole is a Markov process, as it depends on large number of factors operating randomly, and each of its successive steps probably depends randomly on the state of the system in the previous instant. Modeling the exploration process makes it possible to find the dependence of its dynamics on the parameters of the empirical distribution of reserves in the ranking series of deposits. Comparison of districts on the basis of these rankings will enable in the future to improve the planning and control of geological exploration.